Enzymatic Study of Linoleic and Alpha-Linolenic Acids Biohydrogenation by Chloramphenicol-Treated Mixed Rumen Bacterial Species - Meynadier, Annabelle; Zened, Asma; Farizon, Yves; Chemit, Marie-Luce; Enjalbert, Francis (Frontiers in Microbiology, 2018)
In the rumen, alimentary polyunsaturated fatty acids (PUFA) are reduced by multistage reaction called biohydrogenation (BH), increasing saturated fat in ruminant products. On the other hand, some potential bioactive intermediates like conjugated linoleic and linolenic acids could be produced during BH. BH is composed of two kinds of reactions: first an isomerization of PUFA followed by reductions (two for linoleic acid, C18:2n-6; three for alpha-linolenic acid, C18:3n-3). There is little knowledge about BH enzymes as BH bacterial species are the subject of a lot of studies. Nevertheless, both aspects must be explored to control BH and enhancement of the fatty acids profile of ruminant products. In the present study, a new approach was developed to study the enzymes produced in vivo by mixed ruminal bacteria, using inactivation of bacteria by chloramphenicol, an inhibitor of protein synthesis in prokaryotes, before in vitro incubation. To study C18:2n-6 and C18:3n-3 BH several experiments were used: 1) with different incubation durations (0 to 3 h) to estimate average rates and efficiencies of all the BH reactions, and intermediates production; and 2) with different initial quantities of PUFA (0.25 to 2 mg) to estimate Michaelis-Menten enzymatic parameters, Km and Vmax. A last experiment explored the effect of pH buffer and donor cow diet on C18:2n-6 isomerization pathways. Concerning C18:2n-6 BH, this study confirmed the high saturability of its isomerization, the inhibition of both trans11 and trans10 pathways by a low pH, and the last reduction to stearic acid as the limiting-step. Concerning C18:3n-3, its BH was faster than C18:2n-6, in particular its isomerization (Vmax = 3.4 vs. 0.6 mM/h, respectively), and the limiting-step was the second reduction to t11-C18:1. Besides, our mixed isomerases had a higher affinity for C18:2n-6 than for C18:3n-3 (Km = 2.0x10-3 vs. 4.3x10-3 M, respectively), but due to its high saturability by C18:2n-6, they had a lower efficiency to isomerize C18:2n-6 than C18:3n-3. Chloramphenicol-treated ruminal fluid would be a meaningful method to study the BH enzymes activities.